STRUCTURAL TYPES OF UZBEK RADIOCOMMUNICATION TERMS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In this article, the Uzbek language is studied structurally simple terms in the field of radio communication, applied to compound, pair, compound and contractile types, and each type is covered by examples.